An evaluation of the Alliance Theological Education by Extension Program (All-Tee) in Southern Philippines - Mackinnon, Ronald Paul (1986)
This is an evaluation of the Alliance Theological Education of the Extension Program of the Christian and Missionary Alliance Churches of the Philippines, designed to train people for Christian ministry. This is undertaken to determine the status of the program in reaching its objectives and to ascertain what outcomes have resulted in the area of the social relationships of the students.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Alliance Theological Education by Extension Program; Clergy, Training of; Theology -- Study and teaching -- Philippines -- Mindanao